Changes in the Distribution of Children's Family Income Over the 1990's - Blank, Rebecca M; Schoeni, Robert F (American Economic Review, 2003)
Changes in the Distribution of Children's Family Income over the 1990's by Rebecca M. Blank and Robert F. Schoeni. Published in volume 93, issue 2, pages 304-308 of American Economic Review, May 2003